Cubic boron nitride sintered body and tool
By adjusting the content of cubic-crystal boron nitride particles and the composition of the bonded phase in the cubic-crystal boron nitride sintered body, the contact area between the bonded phase particles and the first phase is improved, and the problem of short tool life in high-efficiency processing of high-hardness steel is solved. The tool's wear resistance and defect resistance are improved.
Patent Information
- Application Number
- CN202480002781.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-27
- Filing Date
- 2024-04-26
- Publication Date
- 2024-12-27
AI Technical Summary
In the high-efficiency processing of high-hardness steel, the existing cubic-crystal boron nitride sintered body tools have a short life and are difficult to meet the needs of high-efficiency processing.
By reasonably adjusting the content of cubic boron nitride particles and the composition of the bonding phase in the cubic boron nitride sintered body, ensuring the increase of the contact area between the surface of the bonding phase particles and the first phase, the specific sintering process conditions are used to enhance the tool wear resistance and defect resistance.
The service life of the cubic-crystal boron nitride sintered body tool in high-efficiency processing of high hardness steel is achieved, and the wear resistance and defect resistance of the tool is improved, and the demand for high-efficiency processing is met.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present disclosure relates to a cubic boron nitride sintered body and a tool. This application claims priority based on Japanese Patent Application No. 2023-073631 filed on April 27, 2023. All the contents described in the Japanese patent application are incorporated herein by reference. Background Art
[0002] Cubic boron nitride (hereinafter also referred to as "cBN") sintered bodies have very high hardness and excellent thermal and chemical stability, and are therefore used in cutting tools and wear-resistant tools. In order to obtain properties in accordance with the application in cubic boron nitride sintered bodies, the content of cBN particles and the type of binder phase are studied.
[0003] Patent Document 1 discloses a technology in which, in a cubic boron nitride sintered body including cubic boron nitride particles and Ti compound particles as a binder phase, W—Co phase is present uninterruptedly between cubic boron nitride particles, thereby improving crater wear resistance and chipping resistance.
[0004] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2020-28929 Summary of the invention The cubic boron nitride sintered body disclosed in the present invention comprises cubic boron nitride particles, a binding phase and a first phase, wherein: The content of the cubic boron nitride particles in the cubic boron nitride sintered body is 25% by volume or more and 80% by volume or less. The bonding phase comprises one or more first compounds and one or both of solid solutions derived from the first compounds, wherein the first compounds are composed of at least one element selected from the group consisting of titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, aluminum, and silicon, and at least one element selected from the group consisting of nitrogen, carbon, boron, and oxygen, The first phase comprises cobalt, tungsten and at least one first element selected from the group consisting of the elements comprised by the bonding phase, The total content of cobalt and tungsten in the cubic boron nitride sintered body is 1.0 mass % or more and 6.0 mass % or less, The binding phase is composed of a plurality of binding phase particles, The plurality of binding phase particles include more than 50% of first binding phase particles on a number basis, The surface of the first binding phase particle contains more than 50% by area of the first region, The first region is a region in contact with the first phase.
[0005] The cubic boron nitride sintered body disclosed in the present invention comprises cubic boron nitride particles, a binding phase and a first phase, wherein: The content of the cubic boron nitride particles in the cubic boron nitride sintered body is 25% by volume or more and 80% by volume or less. The bonding phase comprises one or more first compounds and one or both of solid solutions derived from the first compounds, wherein the first compounds are composed of at least one element selected from the group consisting of titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, aluminum, and silicon, and at least one element selected from the group consisting of nitrogen, carbon, boron, and oxygen, The first phase comprises cobalt, tungsten and at least one first element selected from the group consisting of the elements comprised by the bonding phase, The total content of cobalt and tungsten in the cubic boron nitride sintered body is 1.0 mass % or more and 6.0 mass % or less, The binding phase is composed of a plurality of binding phase particles, The plurality of binding phase particles include more than 50% of first binding phase particles on a number basis, The surface of the first binding phase particle contains more than 50% by area of the first region, The first region is a region in contact with the first phase. DETAILED DESCRIPTION
[0006] [Problems to be Solved by the Present Disclosure] In recent years, there has been an increasing demand for efficient machining of high-hardness steel. Therefore, when used as a tool material, a cubic boron nitride sintered body is required that can provide a tool with a long tool life even in efficient machining of high-hardness steel.
[0007] Therefore, an object of the present disclosure is to provide a cubic boron nitride sintered body that, when used as a tool material, can provide a tool with a long tool life even in high-efficiency processing of high-hardness steel, and a tool including the cubic boron nitride sintered body.
[0008] [Effects of the present disclosure] According to the present disclosure, a cubic boron nitride sintered body capable of providing a tool having a long tool life even in high-efficiency machining of high-hardness steel when used as a tool material, and a tool including the cubic boron nitride sintered body can be provided.
[0009] [Description of Embodiments of the Present Disclosure] First, embodiments of the present disclosure will be described by way of examples.
[0010] (1) The cubic boron nitride sintered body disclosed in the present invention comprises cubic boron nitride particles, a binder phase and a first phase, wherein: The content of the cubic boron nitride particles in the cubic boron nitride sintered body is 25% by volume or more and 80% by volume or less. The bonding phase comprises one or more first compounds and one or both of solid solutions derived from the first compounds, wherein the first compounds are composed of at least one element selected from the group consisting of titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, aluminum, and silicon, and at least one element selected from the group consisting of nitrogen, carbon, boron, and oxygen, The first phase comprises cobalt, tungsten and at least one first element selected from the group consisting of the elements comprised by the bonding phase, The total content of cobalt and tungsten in the cubic boron nitride sintered body is 1.0 mass % or more and 6.0 mass % or less, The binding phase is composed of a plurality of binding phase particles, The plurality of binding phase particles include more than 50% of first binding phase particles on a number basis, The surface of the first binding phase particle contains more than 50% by area of the first region, The first region is a region in contact with the first phase.
[0011] According to the present disclosure, a cubic boron nitride sintered body capable of providing a tool having a long tool life even in high-efficiency machining of high-hardness steel when used as a tool material, and a tool including the cubic boron nitride sintered body can be provided.
[0012] (2) In the above (1), the plurality of binder phase particles may include 50% or more of second binder phase particles on a number basis, The surface of the second binding phase particle contains more than 75% by area of the first region.
[0013] As a result, the life of the tool including the cubic boron nitride sintered body is further improved.
[0014] (3) In the above (1) or (2), the binder phase may include at least one element selected from the group consisting of titanium, chromium, aluminum, carbon, nitrogen, and boron. This further improves the life of the tool including the cubic boron nitride sintered body.
[0015] (4) In any one of (1) to (3) above, the first element may include at least one element selected from the group consisting of aluminum, carbon, nitrogen, boron, and silicon. Thus, the life of the tool including the cubic boron nitride sintered body is further improved.
[0016] (5) In any one of the above (1) to (4), the first phase may not exist at the interface between the cubic boron nitride particles and the binder phase. Thus, in intermittent machining under particularly severe conditions, the life of the tool having the cubic boron nitride sintered body is further improved.
[0017] (6) In any one of (1) to (5) above, the thickness of the first phase may be 20 nm or less. Thus, in intermittent machining under particularly severe conditions, the life of a tool including a cubic boron nitride sintered body is further improved.
[0018] (7) In any one of (1) to (6) above, the tungsten content of the first phase may be greater than the cobalt content of the first phase. Thus, in intermittent machining under particularly severe conditions, the life of the tool including the cubic boron nitride sintered body is further improved.
[0019] (8) The tool of the present disclosure is a tool including the cubic boron nitride sintered body of any one of (1) to (7) above. The tool of the present disclosure can have a long tool life even in high-efficiency machining of high-hardness steel.
[0020] [Details of the embodiments of the present disclosure] Specific examples of the cubic boron nitride sintered body and tool disclosed in the present invention are described below. In this specification, expressions such as "A to B" refer to the upper and lower limits of a range (i.e., greater than A and less than B). When there is no unit in A and only a unit in B, the unit of A is the same as the unit of B.
[0021] In the present specification, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, all conventionally known atomic ratios are included, and the atomic ratio is not necessarily limited to the atomic ratio within the stoichiometric range.
[0022] In the present disclosure, when more than one numerical value is recorded as the lower limit and the upper limit of the numerical range, a combination of any numerical value recorded in the lower limit and any numerical value recorded in the upper limit is also disclosed. For example, when more than a1, more than b1, and more than c1 are recorded as the lower limit, and less than a2, less than b2, and less than c2 are recorded as the upper limit, more than a1 and less than a2, more than a1 and less than b2, more than a1 and less than c2, more than b1 and less than a2, more than b1 and less than b2, more than b1 and less than c2, more than c1 and less than a2, more than c1 and less than b2, more than c1 and less than c2 are disclosed.
[0023] [Embodiment 1: Cubic Boron Nitride Sintered Body] A cubic boron nitride sintered body according to one embodiment of the present disclosure (hereinafter also referred to as “embodiment 1”) includes cubic boron nitride particles, a binder phase, and a first phase. The content of cubic boron nitride particles in the cubic boron nitride sintered body is 25% by volume or more and 80% by volume or less. The binding phase comprises one or more first compounds and one or both of solid solutions of the first compounds, wherein the first compound is composed of at least one element selected from the group consisting of titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, aluminum and silicon, and at least one element selected from the group consisting of nitrogen, carbon, boron and oxygen, The first phase includes cobalt, tungsten and at least one first element selected from the group consisting of elements included in the bonding phase, The total content of cobalt and tungsten in the cubic boron nitride sintered body is 1.0 mass % or more and 6.0 mass % or less, The binding phase is composed of a plurality of binding phase particles. The plurality of binding phase particles include more than 50% of the first binding phase particles on a number basis, The surface of the first binding phase particle contains more than 50% by area of the first region, The first region is a region in contact with the first phase.
[0024] When the cubic boron nitride sintered body of the present disclosure is used as a tool material, it is possible to provide a tool having a long tool life even in high-efficiency machining of high-hardness steel. The reason for this is presumably as follows.
[0025] (i) The cubic boron nitride sintered body disclosed herein contains 25% by volume or more and 80% by volume or less of cubic boron nitride particles having excellent strength and toughness. Therefore, the cubic boron nitride sintered body can also have excellent strength and toughness. Therefore, a tool containing the cubic boron nitride sintered body can have excellent wear resistance and defect resistance even in high-efficiency processing of high-hardness steel.
[0026] (ii) In the cubic boron nitride sintered body of the present disclosure, the binding phase includes one or more first compounds and one or both of the solid solutions derived from the first compounds, wherein the first compound is composed of at least one element selected from the group consisting of titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, aluminum and silicon, and at least one element selected from the group consisting of nitrogen, carbon, boron and oxygen. The first compound itself has high strength and high toughness, and improves the bonding force between cBN particles. Therefore, the tool including the cubic boron nitride sintered body containing the first compound as the binding phase can have excellent wear resistance and defect resistance even in high-efficiency processing of high-hardness steel.
[0027] (iii) The cubic boron nitride sintered body disclosed in the present invention contains a first phase, which contains cobalt, tungsten and at least one first element selected from the elements contained in the binding phase. The first phase can improve the bonding force between the binding phase particles. In the cubic boron nitride sintered body disclosed in the present invention, the percentage of the number basis of the first binding phase particles that are in contact with the first phase for more than 50% of the surface relative to the entire binding phase particles is more than 50%, so the bonding force between the binding phase particles is improved. Therefore, the tool containing the cubic boron nitride sintered body disclosed in the present invention can have excellent wear resistance and defect resistance even in high-efficiency processing of high-hardness steel.
[0028] In the present disclosure, as high hardness steel, for example, chrome-molybdenum steel (SCM415) can be cited. In the above, the case where the tool including the cubic boron nitride sintered body of the present disclosure has a long tool life in the high-efficiency processing of high hardness steel is described, but the cut material is not limited to this. As the cut material, for example, high-strength cast iron materials (FCD700, etc.), carbon steel for machine structures (S50C, etc.), high-carbon chromium bearing steel (SUJ2, SUJ4, etc.), or alloy tool steel (SKD11, etc.) can be cited.
[0029] <Composition of Cubic Boron Nitride Sintered Body> The cubic boron nitride sintered body of the first embodiment includes cubic boron nitride particles, a binder phase, and a first phase.
[0030] In the cubic boron nitride sintered body of embodiment 1, the content of cubic boron nitride particles is 25 volume % or more and 80 volume % or less. From the viewpoint of improving hardness, the lower limit of the content of cubic boron nitride particles of the cubic boron nitride sintered body is 25 volume % or more, and it can also be 30 volume % or more, and it can also be 35 volume % or more, and it can also be 40 volume % or more. From the viewpoint of improving toughness, the upper limit of the content of cubic boron nitride particles of the cubic boron nitride sintered body is 80 volume % or less, and it can also be 75 volume % or less, and it can also be 70 volume % or less, and it can also be 65 volume % or less. The content of cubic boron nitride particles of the cubic boron nitride sintered body is 25 volume % or more and 80 volume % or less, and it can also be 25 volume % or more and 75 volume % or less, and it can also be 25 volume % or more and 70 volume % or less, and it can also be 30 volume % or more and 70 volume % or less, and it can also be 40 volume % or more and 65 volume % or less.
[0031] In the present disclosure, the content of cubic boron nitride particles in a cubic boron nitride sintered body is measured using an energy dispersive X-ray analyzer (EDX) ("Octane Elect EDS System" (trademark) manufactured by EDAX) with a scanning electron microscope (SEM) ("JSM-7800F" (trademark) manufactured by JEOL Ltd.) (hereinafter also referred to as "SEM-EDX") according to the following procedure.
[0032] Cut the cubic boron nitride sintered body at any position to expose the cross section of the cubic boron nitride sintered body, and grind the cross section. The cubic boron nitride sintered body can be cut using a focused ion beam device, a cross-section polishing machine device, etc. In the case where the cubic boron nitride sintered body is used as a part of a tool, a portion of the cubic boron nitride sintered body is cut out using a diamond wheel electrodeposition wire, etc., so that a sample containing the cross section of the cubic boron nitride sintered body is exposed.
[0033] Next, the cross section was observed with a SEM at 5000 times magnification to obtain a reflected electron image. In the reflected electron image, the region where the cBN particles exist is a black region, and the region where the binding phase and the first phase exist is a gray region or a white region.
[0034] Next, the reflected electron image was binarized using image analysis software ("WinROOF 2018" from Mitani Shoji Co., Ltd.) to extract only the cBN particles. In the binarized image, the cBN particles are represented by the dark field (black), and the bonding phase and the first phase are represented by the bright field (white). In the binarized image, the area percentage of the pixels derived from the dark field (pixels derived from the cBN particles) relative to the area of the entire measurement field of view was calculated (hereinafter also referred to as the "area percentage of cBN particles").
[0035] The above-mentioned area percentage of cBN particles is measured in five non-overlapping measurement fields, and the average area percentage of cBN particles in the five measurement fields is calculated. In the present disclosure, the average area percentage of cBN particles in the five measurement fields corresponds to the content (volume %) of cubic boron nitride particles in the cubic boron nitride sintered body.
[0036] It was confirmed that within the measurement range of the applicant, even if five measurement fields were arbitrarily set in the same sample and the content of cubic boron nitride particles in the cubic boron nitride sintered body was measured multiple times according to the above procedure, there was almost no deviation in the measurement results.
[0037] The cubic boron nitride sintered body of embodiment 1 may be composed of cubic boron nitride particles, a binding phase and a first phase. In the cubic boron nitride sintered body of embodiment 1, as long as the effect of the present disclosure is not impaired, impurities caused by raw materials, manufacturing conditions, etc. may be included on the basis of the cubic boron nitride particles, the binding phase and the first phase. The cubic boron nitride sintered body of embodiment 1 may be composed of cubic boron nitride particles, a binding phase, a first phase and impurities. As impurities, nickel can be cited, for example. In the case where the cubic boron nitride sintered body contains impurities, the impurity content of the cubic boron nitride sintered body can be set to less than 0.1 mass %. The impurity content of the cubic boron nitride sintered body can be measured by secondary ion mass spectrometry (SIMS).
[0038] <Cubic Boron Nitride Particles> 《Composition of cubic boron nitride particles》 In Embodiment 1, the cubic boron nitride particles are composed of cubic boron nitride. In the cubic boron nitride particles, impurities may be included together with the cubic boron nitride as long as the effects of the present disclosure are not impaired. In the case where the cubic boron nitride particles include impurities, the content of the impurities in the cubic boron nitride particles may be set to 0.1 mass % or less. The content of the impurities in the cubic boron nitride particles can be measured by secondary ion mass spectrometry (SIMS).
[0039] 《Average particle size of cubic boron nitride particles》 In the cubic boron nitride sintered body of Embodiment 1, the average particle size of the cubic boron nitride particles is not particularly limited and can be a general average particle size used in conventional cubic boron nitride sintered bodies. The particle size of the cubic boron nitride particles can be, for example, 0.1 μm to 10 μm.
[0040] In the present disclosure, the average particle size of cubic boron nitride particles is measured by the following procedure: The cross section of the cBN sintered body is exposed and polished by the same method as the procedure for measuring the content of cubic boron nitride particles in a cubic boron nitride sintered body.
[0041] Next, the polished surface was observed with an SEM at 10,000 times to obtain an SEM image. A rectangular measurement field of 12 μm × 15 μm was set in the SEM image. The SEM image was processed using image analysis software ("WinROOF ver.7.4.5" of Mitani Shoji Co., Ltd.) to obtain the equivalent circle diameter of each cBN particle observed in the measurement field of view. The arithmetic mean of the equivalent circle diameters of all cBN particles in the measurement field of view was calculated. The arithmetic mean is equivalent to the average particle size of the cBN particles in the measurement field of view.
[0042] The above measurement is performed in five non-overlapping measurement fields. The arithmetic mean of the average particle size of the cBN particles in the five measurement fields is calculated. In the present disclosure, the arithmetic mean of the average particle size of the five measurement fields corresponds to the average particle size of the cubic boron nitride particles.
[0043] It was confirmed that within the range of the applicant's measurement, even if five measurement fields were arbitrarily set in the same sample and the average particle size of the cubic boron nitride particles was measured multiple times according to the above procedure, there was almost no variation in the measurement results.
[0044] <Combination Phase> In the cubic boron nitride sintered body of embodiment 1, the bonding phase includes one or more first compounds and one or both of the solid solutions derived from the first compounds, and the first compound is composed of at least one element selected from the group consisting of titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum, chromium, molybdenum, aluminum and silicon (hereinafter also referred to as "second element"), and at least one element selected from the group consisting of nitrogen, carbon, boron and oxygen.
[0045] The bonding phase can be in any of the following ways.
[0046] (i) The binding phase comprises a first compound.
[0047] (ii) The binding phase is composed of the first compound.
[0048] (iii) The binding phase comprises a solid solution from the first compound.
[0049] (iv) The binding phase is composed of a solid solution derived from the first compound.
[0050] (v) The combined phase includes the first compound and a solid solution derived from the first compound.
[0051] (vi) The binding phase is composed of the first compound and a solid solution derived from the first compound.
[0052] In the binding phase, impurities may be included together with one or both of the first compound and the solid solution derived from the first compound, as long as the effect of the present disclosure is not impaired. In the case where the binding phase contains impurities, the content of the impurities in the binding phase may be set to 0.1% by mass or less. The content of impurities in the binding phase may be measured by secondary ion mass spectrometry (SIMS).
[0053] Examples of the first compound (nitride) composed of the second element and nitrogen include titanium nitride (TiN), zirconium nitride (ZrN), hafnium nitride (HfN), vanadium nitride (VN), niobium nitride (NbN), tantalum nitride (TaN), chromium nitride (Cr2N), molybdenum nitride (MoN), AlN (aluminum nitride), silicon nitride (Si3N4), titanium zirconium nitride (TiZrN), titanium hafnium nitride (TiHfN), titanium vanadium nitride (TiVN), titanium niobium nitride (TiNbN), titanium tantalum nitride (TiTaN), titanium chromium nitride (TiCrN), titanium molybdenum nitride (TiMoN), zirconium hafnium nitride (ZrHfN), zirconium vanadium nitride (ZrVN), zirconium niobium nitride (ZrNbN ), zirconium tantalum nitride (ZrTaN), zirconium chromium nitride (ZrCrN), zirconium molybdenum nitride (ZrMoN), hafnium vanadium nitride (HfVN), hafnium niobium nitride (HfNbN), hafnium tantalum nitride (HfTaN), hafnium chromium nitride (HfCrN), hafnium molybdenum nitride (HfMoN), vanadium niobium nitride (VNbN), vanadium tantalum nitride (VTaN), vanadium chromium nitride (VCrN), vanadium molybdenum nitride (VMoN), niobium tantalum nitride (NbTaN), niobium chromium nitride (NbCrN), niobium molybdenum nitride (NbMoN), tantalum chromium nitride (TaCrN), tantalum molybdenum nitride (TaMoN), chromium molybdenum nitride (CrMoN), or titanium aluminum nitride (TiAlN, Ti2AlN, Ti3AlN).
[0054] Examples of the first compound (carbide) composed of the second element and carbon include titanium carbide (TiC), zirconium carbide (ZrC), hafnium carbide (HfC), vanadium carbide (VC), niobium carbide (NbC), tantalum carbide (TaC), chromium carbide (Cr2C), molybdenum carbide (MoC), silicon carbide (SiC), titanium zirconium carbide (TiZrC), titanium hafnium carbide (TiHfC), titanium vanadium carbide (TiVC), titanium niobium carbide (TiNbC), titanium tantalum carbide (TiTaC), titanium chromium carbide (TiCrC), titanium molybdenum carbide (TiMoC), zirconium hafnium carbide (ZrHfC), zirconium vanadium carbide (ZrVC), zirconium niobium carbide (ZrNbC), zirconium tantalum carbide (TiMoC), (ZrTaC), zirconium chromium carbide (ZrCrC), zirconium molybdenum carbide (ZrMoC), hafnium vanadium carbide (HfVC), hafnium niobium carbide (HfNbC), hafnium tantalum carbide (HfTaC), hafnium chromium carbide (HfCrC), hafnium molybdenum carbide (HfMoC), vanadium niobium carbide (VNbC), vanadium tantalum carbide (VTaC), vanadium chromium carbide (VCrC), vanadium molybdenum carbide (VMoC), niobium tantalum carbide (NbTaC), niobium chromium carbide (NbCrC), niobium molybdenum carbide (NbMoC), tantalum chromium carbide (TaCrC), tantalum molybdenum carbide (TaMoC), chromium molybdenum carbide (CrMoC), or titanium aluminum carbide (TiAlC, Ti2AlC, Ti3AlC).
[0055] Examples of the first compound (carbonitride) composed of the second element, carbon, and nitrogen include titanium carbonitride (TiCN), zirconium carbonitride (ZrCN), hafnium carbonitride (HfCN), or titanium aluminum carbonitride (TiAlCN, Ti2AlCN, Ti3AlCN).
[0056] Examples of the first compound (boride) composed of a second element and boron include titanium boride (TiB2), zirconium boride (ZrB2), hafnium boride (HfB2), vanadium boride (VB2), niobium boride (NbB2), tantalum boride (TaB2), chromium boride (CrB2), molybdenum boride (MoB2) or silicon boride (SiB4).
[0057] Examples of the first compound (oxide) composed of the second element and oxygen include titanium oxide (TiO2), zirconium oxide (ZrO2), hafnium oxide (HfO2), vanadium oxide (V2O5), niobium oxide (Nb2O5), tantalum oxide (Ta2O5), chromium oxide (Cr2O3), molybdenum oxide (MoO3), aluminum oxide (Al2O3), or silicon oxide (SiO2).
[0058] Examples of the first compound (oxynitride) composed of the second element, nitrogen and oxygen include titanium oxynitride (TiON), zirconium oxynitride (ZrON), hafnium oxynitride (HfON), vanadium oxynitride (VON), niobium oxynitride (NbON), tantalum oxynitride (TaON), chromium oxynitride (CrON), molybdenum oxynitride (MoON) or SiAlON.
[0059] The bonding phase may include at least one element selected from the group consisting of titanium, chromium, aluminum, carbon, nitrogen, and boron.
[0060] The first compound may be composed of at least one selected from the group consisting of TiN, TiCN, TiC, CrN, AlCrN, and Al 2 O 3. The first compound may be used alone or in combination of two or more.
[0061] The binding phase may include a solid solution derived from the first compound. Here, the solid solution derived from the first compound refers to a state in which two or more first compounds are dissolved in each other's crystal structure, and refers to an intrusive solid solution or a substitutional solid solution.
[0062] In the present disclosure, the composition of the binder phase is identified by the following procedure using X-ray diffraction: The cross section of the cBN sintered body is exposed and polished by the same method as the procedure for measuring the content of cubic boron nitride particles in the cubic boron nitride sintered body.
[0063] An X-ray diffraction spectrum of the polished surface was obtained using an X-ray diffraction apparatus ("MiniFlex600" (trademark) manufactured by Rigaku Corporation). The conditions of the X-ray diffraction apparatus are as follows.
[0064] Characteristic X-ray: Cu-Kα (wavelength 1.54Å) Tube voltage: 45kV Tube current: 40mA Filter: Multilayer mirror Optical system: Concentration method X-ray diffraction method: θ-2θ method.
[0065] Based on the obtained X-ray diffraction spectrum, the composition of the bound phase was identified.
[0066] <First Phase> In the cubic boron nitride sintered body of embodiment 1, the first phase contains cobalt, tungsten and at least one first element selected from the group consisting of elements contained in the binding phase. The first element is an element other than tungsten among the elements contained in the binding phase. The first element is at least one element selected from the group consisting of the same elements as the elements contained in the binding phase, which are selected from titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, aluminum, silicon, nitrogen, carbon, boron and oxygen. For example, in the case where the binding phase is composed of TiCN, the first element is at least one element selected from the group consisting of Ti, C and N. The first phase can improve the bonding force between the binding phase particles by further containing at least one element that is the same as the element contained in the binding phase in addition to cobalt and tungsten.
[0067] The first element may include at least one element selected from the group consisting of aluminum, carbon, nitrogen, boron, and silicon. Thus, the bonding force between the bonding phase particles is further improved.
[0068] In the present disclosure, the fact that the cubic boron nitride sintered body includes the first phase is confirmed by the following procedure.
[0069] (A1) A sample was collected from a cubic boron nitride sintered body, and the sample was sliced into a thickness of 30 to 100 nm using an argon ion microtome to prepare a slice. Then, the slice was observed using a transmission electron microscope (TEM) ("JEM-2100F / Cs" (trademark) manufactured by JEOL Ltd.) at 10,000 times to obtain a TEM image.
[0070] (A2) Based on the TEM image, an element mapping image of cobalt and an element mapping image of tungsten were obtained using an energy dispersive X-ray analyzer (EDX) equipped with TEM ("EDAX" (trademark) manufactured by AMETEK Corporation).
[0071] (A3) Using image analysis processing software ("WinROOF 2018" by Mitani Shoji Co., Ltd.), the element mapping image of cobalt and the element mapping image of tungsten are overlapped. In the overlapped image (hereinafter also referred to as "image A"), a region where cobalt and tungsten continuously coexist (hereinafter also referred to as "W-Co region") is identified.
[0072] (A4) Based on the results of measuring the composition of the binder phase by X-ray diffraction, the elements constituting the binder phase are determined. Based on the TEM image of the same field of view as in (A1), elemental mapping analysis is performed using an electron energy loss spectroscopy (EELS) analyzer attached to the TEM to obtain an elemental mapping image of each element (hereinafter also referred to as "image B").
[0073] (A5) Using image analysis processing software, the image A of (A3) is overlapped with the image B of (A4). In the overlapped image (hereinafter also referred to as "image C"), when at least one of the elements constituting the bonding phase identified by image B coexists in the W-Co region of image A, it is confirmed that the cubic boron nitride sintered body includes the first phase.
[0074] In the cubic boron nitride sintered body of embodiment 1, the total content of cobalt and tungsten in the cubic boron nitride sintered body is 1.0 mass % or more and 6.0 mass % or less. From the viewpoint of improving the bonding force between the bonding phase particles, the lower limit of the total content of cobalt and tungsten in the cubic boron nitride sintered body is 1.0 mass % or more, or 1.4 mass % or more, or 1.5 mass % or more, or 1.8 mass % or more, or 2.0 mass % or more, or 2.5 mass % or more, or 3.0 mass % or more. From the viewpoint of suppressing the reduction in wear resistance caused by the coarsening of the first phase, the upper limit of the total content of cobalt and tungsten in the cubic boron nitride sintered body is 6.0 mass % or less, or 5.8 mass % or less, or 5.7 mass % or less, or 5.5 mass % or less, or 5.2 mass % or less, or 5.0 mass % or less, or 4.5 mass % or less, or 4.0 mass % or less. The total content of cobalt and tungsten in the cubic boron nitride sintered body can be greater than 1.4 mass % and less than 5.8 mass %, or greater than 1.5 mass % and less than 5.7 mass %, or greater than 1.8 mass % and less than 5.5 mass %, or greater than 2.0 mass % and less than 5.2 mass %, or greater than 2.5 mass % and less than 5.0 mass %, or greater than 3.0 mass % and less than 4.5 mass %.
[0075] In the present disclosure, the total content of cobalt and tungsten in the cubic boron nitride sintered body on a mass basis is measured by ICP mass spectrometry.
[0076] <Thickness of the First Phase> In the cubic boron nitride sintered body of the first embodiment, the thickness of the first phase may be 20 nm or less, 0.6 nm or more and 20 nm or less, or 5 nm or more and 10 nm or less.
[0077] In the present disclosure, the thickness of the first phase is confirmed by the following steps. The first phase is determined by the same steps (A1) to (A5) as the confirmation method for the cubic boron nitride sintered body containing the first phase, and in the TEM image, EDX is used for line analysis in the direction perpendicular to the extension direction of the first phase. The half-value width of the tungsten peak is taken as the thickness of the first phase. In the first phase of any 10 different parts, the thickness of the first phase is measured and the average value is calculated. However, when the thickness of the first phase is less than 0.5nm, it is excluded from the calculation of the average value as noise. In the present disclosure, the average value is equivalent to the thickness of the first phase. It is confirmed that as long as the same cubic boron nitride sintered body is used for measurement, even if the measurement site is changed, roughly the same result can be obtained.
[0078] <Tungsten Content and Cobalt Content of the First Phase> In the cubic boron nitride sintered body of the first embodiment, the tungsten content of the first phase may be larger than the cobalt content of the first phase.
[0079] In the present disclosure, the tungsten content and cobalt content of the first phase are measured by the following steps. Line analysis of the first phase is performed in the same steps as the method for measuring the thickness of the first phase. The content (atomic %) in the tungsten peak is regarded as the tungsten content of the first phase. The content (atomic %) in the cobalt peak is regarded as the cobalt content of the first phase. In the first phase of any 10 different parts, the tungsten content and the cobalt content are measured, and the respective averages are calculated. In the present disclosure, the average tungsten content is equivalent to the tungsten content of the first phase. In the present disclosure, the average cobalt content is equivalent to the cobalt content of the first phase. It is confirmed that as long as the same cubic boron nitride sintered body is used for measurement, even if the measurement site is changed, approximately the same result can be obtained.
[0080] <Binding Phase Particles> In the cubic boron nitride sintered body of embodiment 1, the binding phase is composed of a plurality of binding phase particles. The plurality of binding phase particles include more than 50% of the first binding phase particles on a number basis. The surface of the first binding phase particles includes more than 50% of the first region by area. The first region is a region in contact with the first phase. In the cubic boron nitride sintered body of embodiment 1, the percentage of the first binding phase particles in contact with the first phase by more than 50% of the surface area relative to the entire binding phase particles is more than 50%, so the binding force between the binding phase particles is improved.
[0081] From the viewpoint of improving the bonding force between the binding phase particles, the lower limit of the percentage of the number basis of the first binding phase particles relative to the entire binding phase particles is 50% or more, or 55% or more, or 60% or more, or 70% or more, or 75% or more, or 80% or more, or 95% or more. The percentage of the number basis of the first binding phase particles relative to the entire binding phase particles may also be 100%.
[0082] In the cubic boron nitride sintered body of Embodiment 1, the plurality of binder phase particles may include more than 50% of the second binder phase particles by number, and the surface of the second binder phase particles may include more than 75% by area of the first region. Thus, the bonding force between the binder phase particles is further improved.
[0083] From the viewpoint of improving the bonding force between the binding phase particles, the lower limit of the percentage of the number basis of the second binding phase particles relative to the entire binding phase particles can be 50% or more, 55% or more, 60% or more, 70% or more, 75% or more, 80% or more, 95% or more, or 95% or more. The percentage of the number basis of the second binding phase particles relative to the entire binding phase particles can also be 100%.
[0084] In the present disclosure, the content rate (percentage) of the first binder phase particles in a plurality of binder phase particles of a cubic boron nitride sintered body based on the number of particles and the content rate (percentage) of the second binder phase particles in a plurality of binder phase particles of a cubic boron nitride sintered body based on the number of particles are measured by using an energy dispersive X-ray analyzer (EDX) ("EDAX" (trademark) manufactured by AMETEK) with a transmission electron microscope (TEM) ("JEM-2100F / Cs" (trademark) manufactured by JEOL Ltd.) according to the following procedure.
[0085] (B1) A sample was collected from a cubic boron nitride sintered body, and sliced into a thickness of 30 to 100 nm using an argon ion microtome to prepare a slice. The slice was then observed using a TEM at 10,000 times magnification to obtain a TEM image.
[0086] (B2) Based on the results of the composition of the binder phase measured by X-ray diffraction, the elements constituting the binder phase are determined. For each element constituting the binder phase, element mapping analysis is performed using EDX to obtain an element mapping image of each element. Furthermore, an element mapping image of cobalt is obtained in the same field of view.
[0087] (B3) Using image analysis processing software ("WinROOF 2018" by Mitani Shoji Co., Ltd.), the element mapping images of the elements constituting the binder phase are overlapped to extract the overlapping area of the elements. The element mapping image of cobalt is overlapped on the extracted area. The area in the extracted area where cobalt does not overlap is the area corresponding to the binder phase.
[0088] (B4) In a TEM image of the same field of view as the elemental mapping image of (B2) above, the crystal orientation of the region corresponding to the binder phase determined in (B3) above is measured using a crystal orientation analyzer with TEM ("ASTER (ACOM)" (trademark) manufactured by Nano Megas) and image analysis processing software ("DIM ver.8" manufactured by TSL with TEM). The crystal orientation of adjacent points of the measurement point that differ by 5 degrees or more is defined as a grain boundary, and the portion other than the grain boundary is defined as a grain. In this way, the grain boundary between the binder phase particles can be determined.
[0089] In addition, in the TEM image of the same field of view as the elemental mapping image (B2) above, the grain boundaries between the bonding phase grains can also be determined by performing binarization processing and particle segmentation processing using image analysis processing software ("WinROOF 2018" of Mitani Shoji Co., Ltd.). In the binarized image obtained here (hereinafter also referred to as "image 1A"), the pixel value of the grain boundary is 255, and the pixel value of the other area is 0.
[0090] (B5) The image obtained in (B4) above in which the grain boundaries between the binding phase particles are determined is binarized using image analysis processing software ("WinROOF 2018" of Mitani Shoji Co., Ltd.), thereby obtaining an image in which the grain boundaries between the binding phase particles are extracted (hereinafter also referred to as the "first image"). In the first image, the pixel value of the grain boundary is 255, and the pixel value of the area other than this is 0. In addition, in the following steps, the 1A image obtained in (B4) above may be used instead of the first image.
[0091] (B6) In the TEM image of the same field of view as the above-mentioned first image (or 1A image), an elemental mapping image of tungsten and an elemental mapping image of cobalt are obtained using EDX. The elemental mapping image of tungsten and the elemental mapping image of cobalt are binarized using image analysis processing software. In the image obtained by binarizing the elemental mapping image of tungsten (hereinafter also referred to as the "second image"), the value of the pixels in the area where tungsten exists is 255, and the value of the pixels in the other areas is 0. In the image obtained by binarizing the elemental mapping image of cobalt (hereinafter also referred to as the "third image"), the value of the pixels in the area where cobalt exists is 255, and the value of the pixels in the other areas is 0.
[0092] (B7) Using image analysis software, the second image and the third image are overlapped, and in the overlapped image (hereinafter also referred to as the "fourth image"), a region where the pixel value is 255 (hereinafter also referred to as the "W—Co phase") is identified.
[0093] Instead of (B6) and (B7), the slice of (B1) may be observed at a magnification of 10 million times under TEM. In this way, an image in which the W—Co phase is confirmed can be obtained (hereinafter also referred to as “image 4A”).
[0094] (B8) Using image analysis processing software, a rectangular measurement field of 12 μm×15 μm is set in the first image (or 1A image). For each of all the binder phase particles in the measurement field, the length L1 of the grain boundary of the outer edge of the specified binder phase particle is measured. The first image (or 1A image) and the fourth image (or the 4A image whose magnification is consistent with the first image) are overlapped. A measurement field of the same area as above is set in the overlapped image. For each of all the binder phase particles in the measurement field, the length L2 of the W-Co phase present at the position overlapping with the grain boundary of the outer edge of the specified binder phase particle is measured. For each of the binder phase particles, the percentage (L2 / L1)×100 of L2 relative to L1 is calculated. In the present disclosure, the percentage (L2 / L1)×100 is equivalent to the coverage of the first area of the surface of the binder phase particle. The binder phase particle with a percentage (L2 / L1)×100 of 50% or more is equivalent to the first binder phase particle. The binding phase particles with a percentage (L2 / L1)×100 of 75% or more correspond to the second binding phase particles. In addition, near the outer edge of the measurement field of view, a part of the binding phase particles sometimes exist outside the measurement field of view. Only the binding phase particles whose entirety exists inside the measurement field of view are taken as the measurement object. In the case where a part of the binding phase particles exists outside the measurement field of view, the binding phase particles are excluded from the measurement object.
[0095] (B9) Calculate the percentage (N2 / N1)×100 of the number N2 of the first binder phase particles relative to the number N1 of all binder phase particles in the measurement field of view. The measurement of the percentage (N2 / N1)×100 is performed in three measurement fields that do not overlap each other. Calculate the arithmetic average of the percentages (N2 / N1)×100 of the three measurement fields of view. In the present disclosure, the arithmetic average of the percentages (N2 / N1)×100 of the three measurement fields of view is equivalent to the content rate (percentage) of the number basis of the first binder phase particles in the plurality of binder phase particles of the cubic boron nitride sintered body.
[0096] (B10) Calculate the percentage (N3 / N1)×100 of the number N3 of the second binder phase particles relative to the number N1 of all binder phase particles in the measurement field of view. The measurement of the percentage (N3 / N1)×100 is performed in three measurement fields that do not overlap each other. Calculate the arithmetic average of the percentages (N3 / N1)×100 of the three measurement fields of view. In the present disclosure, the arithmetic average of the percentages (N3 / N1)×100 of the three measurement fields of view is equivalent to the content rate (percentage) of the second binder phase particles in the plurality of binder phase particles of the cubic boron nitride sintered body based on the number.
[0097] It was confirmed that, within the range of measurement performed by the applicant, even if the position of the measurement field is arbitrarily set and a plurality of measurements are performed on the same cubic boron nitride sintered body, there is almost no variation in the results.
[0098] <Average Particle Size of Binder Phase Particles> In the cubic boron nitride sintered body of Embodiment 1, the average particle size of the binder phase particles is not particularly limited and can be a general average particle size used in conventional cubic boron nitride sintered bodies. The particle size of the binder phase particles can be, for example, 50 nm to 200 μm.
[0099] In the present disclosure, the average particle size of the binder phase particles is measured according to the following procedure. The first image in which the grain boundaries between the binder phase particles are determined as described in (B5) above is obtained by the same method as the method for measuring the content (percentage) of the first binder phase particles in the plurality of binder phase particles of the cubic boron nitride sintered body based on the number of the first binder phase particles.
[0100] Next, a rectangular measurement field of 12 μm × 15 μm was set in the first image. The first image was processed using image analysis software ("WinROOF ver.7.4.5" of Mitani Shoji Co., Ltd.) to obtain the equivalent circle diameter of each binding phase particle observed in the measurement field. The arithmetic mean of the equivalent circle diameters of all binding phase particles in the measurement field was calculated. This arithmetic mean is equivalent to the average particle size of the binding phase particles in the measurement field.
[0101] The above measurement is performed in five non-overlapping measurement fields. The arithmetic mean of the average particle diameters of the binding phase particles in the five measurement fields is calculated. In the present disclosure, the arithmetic mean of the average particle diameters of the five measurement fields is equivalent to the average particle diameter of the binding phase particles.
[0102] It was confirmed that within the measurement range of the applicant, even if five measurement fields were arbitrarily set in the same sample and the average particle size of the binder phase particles was measured multiple times according to the above procedure, there was almost no variation in the measurement results.
[0103] <Presence or absence of the first phase at the interface between cubic boron nitride particles and the binder phase> The first phase may not exist at the interface between the cubic boron nitride particles and the binding phase.
[0104] In the present disclosure, whether the first phase exists at the interface between the cubic boron nitride particles and the binding phase is determined by the following steps.
[0105] The binder phase and the W—Co phase (corresponding to the first phase) are identified in the TEM image by the same method as the method for measuring the number-based content (percentage) of the first binder phase particles in the plurality of binder phase particles in the cubic boron nitride sintered body.
[0106] The same TEM images as above were subjected to elemental mapping of boron and nitrogen. Using the above-mentioned image analysis processing software, the elemental mapping images of boron and nitrogen were overlapped, and the overlapping area of each element was extracted as cubic boron nitride particles. The elemental mapping images of each element constituting the binding phase were overlapped with the extracted area to determine the existence area of the cubic boron nitride particles and the binding phase.
[0107] In the direction perpendicular to the extension direction of the interface between any cubic boron nitride particle and a particle of the binding phase adjacent thereto, at 10 locations equally divided relative to the length of the extension direction of the interface, EDX is used for line analysis. When there is no first phase with a thickness of 0.5 nm or more between the cubic boron nitride particle and a particle of the binding phase at more than 8 of the 10 locations, it is judged that there is no first phase at the interface between the cubic boron nitride particle and the binding phase. The following situation is confirmed: as long as the same cubic boron nitride sintered body is used for measurement, even if the measurement location is changed, substantially the same result can be obtained.
[0108] <Method for producing cubic boron nitride sintered body> The method for producing a cubic boron nitride sintered body according to Embodiment 1 will be described. The method for producing a cubic boron nitride sintered body according to Embodiment 1 may include, for example, a raw material preparation step, a mixing step, and a sintering step.
[0109] 《Raw material preparation process (1)》 As raw materials for the cubic boron nitride sintered body, cubic boron nitride powder (hereinafter also referred to as "cBN powder") and binder raw material powder are prepared. The cBN powder is not particularly limited, and known cBN powder can be used. The average particle size of the cBN powder is not particularly limited, and can be, for example, 0.1 to 12.0 μm.
[0110] As a raw material of the binder phase, a binder phase raw material powder containing elements constituting the binder phase is prepared. The binder phase raw material powder, acetone or ethanol as a solvent, and a cemented carbide ball are put into a container made of cemented carbide and mixed (hereinafter also referred to as "first mixing"). The cemented carbide contains tungsten carbide (WC) and cobalt (Co), for example, WC-6%Co. In the first mixing, at least any one of the following conditions A to C is adopted.
[0111] A. The mixing time is set to 120 hours or more and 240 hours or less.
[0112] B. Use a cemented carbide ball whose surface is coated with cobalt powder.
[0113] C. Use a cemented carbide ball with a particle size of 3 mm or more and 10 mm or less, which is larger than the normal particle size.
[0114] 《Mixing process (1)》 Following the raw material preparation step (1), cBN powder, the bonding material raw material powder mixed in a ball mill, acetone or ethanol, and balls are placed in a container made of cemented carbide and mixed (hereinafter also referred to as "second mixing"). In the second mixing, at least one of the following conditions D to F is adopted.
[0115] D. Use a cemented carbide ball with a particle size of 0.5 mm or more and 3 mm or less, which is smaller than the normal particle size.
[0116] E. When using cBN powders of different particle sizes as raw materials, first mix the cBN powder with a smaller particle size and the binder raw material powder. After 3 to 12 hours, add the cBN powder with a larger particle size and mix them.
[0117] F. Use a ball made of something other than cemented carbide as the ball. Examples of a ball made of something other than cemented carbide include a ball made of silicon nitride or alumina.
[0118] The solvent is removed by natural drying after mixing, and then heat-treated to volatilize impurities such as moisture adsorbed on the surface of the mixed powder, thereby cleaning the surface of the mixed powder.
[0119] 《Raw material preparation process (2)》 Instead of the raw material preparation step (1), first mixing may be performed under the following condition G, and a coating process may be performed to form a coating of the target composition on the first mixed powder under the conditions described in the coating process described below.
[0120] G. Use a φ2.0 mm hard alloy ball and set the mixing time to 24 to 90 hours.
[0121] Coverage Processing Covering device: Nanoparticle formation device APD-P ADVANCE Riko Co., Ltd. Target: W is 30~60 atomic %, Co is 70~40 atomic % Introduced gas: Ar Film forming pressure: 0.88Pa Discharge voltage: 150V Discharge frequency: 6Hz Capacitor capacity: 1080μF Number of shots: 1000 to 10000 Powder container speed: 50rpm Processing powder amount: 30g 《Mixing process (2)》 Following the above-mentioned raw material preparation step (2), a second mixing is performed under the following conditions H instead of the above-mentioned mixing step (1).
[0122] H. Use a φ2.0 mm hard alloy ball and set the mixing time to 6 to 12 hours.
[0123] 《Sintering process》 The mixed powder is placed in contact with a WC-6%Co cemented carbide disk and then filled into a container made of Ta (tantalum) and vacuum sealed. The vacuum-sealed mixed powder is sintered using a belt-type ultra-high pressure and high temperature generator under the conditions of 3 GPa to 12 GPa and 1100°C to 2200°C for 5 minutes to 30 minutes. Thus, a cubic boron nitride sintered body of Embodiment 1 is produced.
[0124] In the manufacturing method of patent document 1, in order to form a W-Co phase in a cubic boron nitride sintered body, in the manufacturing process, nano W powder with an average particle size of 500nm~900nm and nano Co powder with an average particle size of 20nm~40nm are added to cBN powder and Ti compound particle powder and mixed, and the mixed powder is sintered to make a cubic boron nitride sintered body. The inventor of the present invention has conducted research. In the manufacturing method of patent document 1, if the total content of cobalt and tungsten in the cubic boron nitride sintered body is a small amount of 1.0 mass % or more and 6.0 mass % or less, the surface of the binding phase particles is small. The area in contact with the W-Co phase is small, and the content of the binding phase particles of the cubic boron nitride sintered body, which has more than 50% of its surface area in contact with the first phase, is less than 50%. In addition, it is confirmed that in the manufacturing method of patent document 1, the W-Co phase does not contain the elements contained in the binding phase.
[0125] As a result of in-depth research conducted by the inventors of the present invention, it was found that by adopting at least any one of the above-mentioned A~C and at least any one of D~F, or the above-mentioned G and covering treatment, and the condition of H, the area where the surface of the bonding phase particles is in contact with the first phase can be increased, the content of bonding phase particles in the bonding phase particles of the cubic boron nitride sintered body with more than 50 area% of its surface in contact with the first phase can be made to be more than 50%, and the first phase can contain tungsten and cobalt while containing the elements contained in the bonding phase.
[0126] It is speculated that by adopting at least any one of the above conditions A to C, tungsten and cobalt contained in the cemented carbide container and the cemented carbide ball are easily in contact with the surface of the binder phase particles, and the surface of the binder phase particles is easily reacted with the first phase.
[0127] By adopting at least one of the above conditions D to F, the crushing of cBN particles during mixing can be suppressed, and the reactivity of the crushed small cBN particles with tungsten and cobalt constituting the first phase during sintering can be suppressed. As a result, the binder phase particles can react with tungsten and cobalt more efficiently.
[0128] [Implementation method 2: Tools] A tool according to one embodiment of the present disclosure (hereinafter also referred to as "embodiment 2") is a tool comprising the cubic boron nitride sintered body of embodiment 1. Each tool may be composed entirely of the cubic boron nitride sintered body, or only a portion thereof (for example, a cutting edge portion in the case of a cutting tool) may be composed of the cubic boron nitride sintered body. Furthermore, a coating film may be formed on the surface of each tool.
[0129] Examples of the cutting tool include drills, end mills, indexable cutting inserts for drills, indexable cutting inserts for end mills, indexable cutting inserts for milling, indexable cutting inserts for turning, metalworking saws, gear cutting tools, reamers, taps, cutting tools, and the like.
[0130] Examples of the wear-resistant tool include a die, a scriber, a scribing wheel, a dresser, etc. Examples of the grinding tool include a grinding grindstone, etc.
[0131] Example The present embodiment will be described in more detail by way of examples, but the present embodiment is not limited to these examples.
[0132] <Production of Cubic Boron Nitride Sintered Body> A cubic boron nitride sintered body of each sample was produced according to the following procedure.
[0133] 《Raw material preparation process》 Cubic boron nitride powder and binder phase raw material powder are prepared. In the sample using condition E in the mixing step described later, two kinds of cubic boron nitride powders with different average particle sizes are prepared. The composition of the binder phase raw material powder is selected so that the binder phase of the produced cubic boron nitride sintered body contains the elements listed in the "Composition" column of "Binding Phase" in Table 2.
[0134] The binder raw material powder, acetone or ethanol as a solvent, and a cemented carbide ball are placed in a cemented carbide container and mixed under any of the following conditions A to C and G. The conditions used in each sample are shown in the "First Mixing" column of Table 1.
[0135] A. The mixing time is set to 120 hours or more and 240 hours or less. A 2.0 mm φ cemented carbide ball is used.
[0136] B. A cemented carbide ball (φ2.0 mm) with a surface coated with cobalt powder was used. The mixing time was set to 96 hours.
[0137] C. Use a cemented carbide ball with a diameter of 3 mm or more and 10 mm or less. The mixing time was set to 96 hours.
[0138] G. Use a φ2.0 mm hard alloy ball and set the mixing time to 24 to 90 hours.
[0139] Next, in Samples 26 to 32, the powder after the first mixing was subjected to a covering treatment under the conditions described in Treatment I or Treatment J below.
[0140] Processing I Covering device: Nanoparticle formation device APD-P ADVANCE Riko Co., Ltd. Target: W 60 atomic %, Co 40 atomic % Introduced gas: Ar Film forming pressure: 0.88Pa Discharge voltage: 150V Discharge frequency: 6Hz Capacitor capacity: 1080μF Number of shots: 1000 to 10000 Powder container speed: 50rpm Processing powder amount: 30g Processing J In process J, only the target of process I is changed to the following.
[0141] Target: W 30 atomic %, Co 70 atomic % 《Mixing process》 cBN powder, the binder raw material powder mixed by a ball mill, acetone or ethanol, and balls were placed in a container made of cemented carbide and mixed under any of the following conditions D to F and H. The conditions used in each sample are shown in the "Second Mixing" column of Table 1.
[0142] D. Use a hard alloy ball with a diameter of 0.5 mm or more and 3 mm or less. The mixing time is 6 to 24 hours.
[0143] E. First, cBN powder with a small particle size is mixed with the binder raw material powder. After 12 hours, cBN powder with a large particle size is added and mixed. A 2.0 mm φ cemented carbide ball is used.
[0144] F. Use a ball other than 2.0 mm hard alloy. Mixing time is 6 to 24 hours.
[0145] H. Use a φ2.0 mm hard alloy ball and set the mixing time to 6 to 12 hours.
[0146] The mixing ratio of each raw material powder was adjusted so that the content (volume %) of the cubic boron nitride particles in the cubic boron nitride sintered body of each sample and the total content (mass %) of tungsten and cobalt in the cubic boron nitride sintered body were as shown in the "cBN particle content" column and the "W+Co content" column of the "Cubic boron nitride sintered body" in Table 2.
[0147] The mixed powder is naturally dried and then heat-treated to volatilize impurities such as moisture adsorbed on the surface of the mixed powder, thereby cleaning the surface of the mixed powder.
[0148] 《Sintering process》 The mixed powder was placed in contact with a WC-6%Co carbide disk and then filled into a container made of Ta (tantalum) and vacuum sealed. The vacuum-sealed mixed powder was sintered using a belt-type ultra-high pressure and high temperature generator under the conditions of 3 GPa to 12 GPa and 1100°C to 2200°C for 5 minutes to 30 minutes. Thus, a cubic boron nitride sintered body of each sample was prepared. The tool shape of the cubic boron nitride sintered body was DNGA150408.
[0149]
[0150] <Evaluation of Cubic Boron Nitride Sintered Body> 《Content ratio of cubic boron nitride particles》 In the cubic boron nitride sintered body of each sample, the content of cubic boron nitride particles in the cubic boron nitride sintered body was measured using SEM-EDX. The specific measurement method is as described in Embodiment 1. The results are shown in the "cBN particle content" column of "Cubic boron nitride sintered body" in Table 2.
[0151] 《Average particle size of cubic boron nitride particles》 It was confirmed that in the cubic boron nitride sintered bodies of all samples, the average particle size of the cubic boron nitride particles was 0.1 μm or more and 10 μm or less.
[0152] Composition of the combined phase In the cubic boron nitride sintered body of each sample, the composition of the binder phase was identified using the X-ray diffraction method. The specific identification method is as described in Embodiment 1. The results of the elements contained in the binder phase are shown in the "Binder Phase Composition" column of Table 2.
[0153] 《The existence of the first phase and the type of the first element contained in the first phase》 For each sample of the cubic boron nitride sintered body, confirm whether the cubic boron nitride sintered body contains the first phase. The specific confirmation method is as described in Implementation Example 1. The results are shown in the "Presence / Absence" column of "First Phase" in Table 2. "Presence" means that the cubic boron nitride sintered body contains the first phase, and "Absence" means that the cubic boron nitride sintered body does not contain the first phase. For the sample with the first phase as "Presence", the first element contained in the first phase is shown in the "First Element" column of "First Phase" in Table 2.
[0154] <<Content ratio of first binding phase particles and content ratio of second binding phase particles>> For each sample of the cubic boron nitride sintered body, the content of the first binder phase particles based on the number of binder phase particles and the content of the second binder phase particles based on the number of binder phase particles were measured. The specific confirmation method is as described in Implementation 1. The results are shown in the "First binder phase particles" and "Second binder phase particles" columns of "Binding phase" in Table 2.
[0155] 《Total content of cobalt and tungsten in cubic boron nitride sintered body》 The total content of cobalt and tungsten was measured for the cubic boron nitride sintered body of each sample. The specific measurement method is as described in Embodiment 1. The results are shown in the column "W+Co content" of Table 2.
[0156]
[0157] <Evaluation of the tool> 《Sample 1~Sample 6, Sample 103, Sample 104》 The following cutting test 1 and cutting test 2 were performed using tools (shape: DNGA150408) composed of cubic boron nitride sintered bodies of samples 1 to 6, sample 103, and sample 104, in which the content of cubic boron nitride particles in the cubic boron nitride sintered bodies was 25 volume % or more and 45 volume % or less. The conditions of cutting test 1 and cutting test 2 correspond to high-efficiency machining of high-hardness steel.
[0158] Cutting test 1: Evaluation of chip resistance Cutting material: High hardness steel SCM415H round bar, five grooves, HRC62, diameter 100mm × length 300mm Cutting speed: V = 150m / min. Feed: f = 0.08 mm / rev. Incision: ap = 0.1 mm Wet / Dry: Dry Cutting method: intermittent cutting The blade tip is observed every 0.15km of cutting distance, and the amount of blade tip shedding is measured. The amount of blade tip shedding is set as the retreat amplitude in the back tool face direction caused by wear from the position of the blade tip ridgeline before cutting. In the case of a defect, the size of the defect is taken as the amount of shedding. The cutting evaluation is terminated at the time point when the amount of blade tip shedding exceeds 0.04mm or the cutting distance is 5.0km, and the amount of blade tip shedding is measured. The smaller the amount of shedding, the better the defect resistance and the longer the tool life. In "Cutting Test 1" in Table 3, the case where the amount of blade tip shedding is less than 0.04mm when the cutting distance is 5.0km is recorded as "A", and the case where the amount of blade tip shedding exceeds 0.04mm before the cutting distance reaches 5.0km or the case where the amount of blade tip shedding exceeds 0.04mm when the cutting distance is 5.0km is recorded as "B". "A" indicates excellent defect resistance and long tool life. "B" indicates insufficient defect resistance and short tool life.
[0159] Cutting test 2: Wear resistance evaluation Cutting material: High hardness steel SCM415H round bar, no groove, HRC62, diameter 100mm × length 300mm Cutting speed: V = 120m / min. Feed: f = 0.1 mm / rev. Incision: ap = 0.1 mm Wet / Dry: Wet Cutting method: continuous cutting The blade tip is observed every 0.5 km of cutting distance, and the amount of blade tip shedding is measured. The amount of blade tip shedding is set as the retreat amplitude in the back tool face direction caused by wear from the position of the blade tip ridgeline before cutting. The cutting evaluation is terminated when the blade tip shedding exceeds 0.04 mm or the cutting distance is 10.0 km, and the amount of blade tip shedding is measured. The smaller the amount of shedding, the better the wear resistance and the longer the tool life. In "Cutting Test 2" in Table 3, the case where the blade tip shedding is less than 0.04 mm when the cutting distance is 10.0 km is recorded as "A", and the case where the blade tip shedding exceeds 0.04 mm before the cutting distance reaches 10.0 km or the blade tip shedding exceeds 0.04 mm when the cutting distance is 10.0 km is recorded as "B". "A" indicates excellent wear resistance and long tool life. "B" indicates insufficient wear resistance and short tool life.
[0160] In this embodiment, when the results of both cutting test 1 and cutting test 2 are "A", the tool life is determined to be long. When the results of one or both of cutting test 1 and cutting test 2 are "B", the tool life is determined to be insufficient.
[0161]
[0162] The cubic boron nitride sintered bodies and tools of samples 1 to 6 correspond to the examples, and the cubic boron nitride sintered bodies and tools of samples 103 and 104 correspond to the comparative examples. It was confirmed that the tools of samples 1 to 6 were excellent in defect resistance and wear resistance, and the tool life was long. It was confirmed that the tools of samples 103 and 104 were insufficient in defect resistance and wear resistance, and the tool life was insufficient.
[0163] 《Sample 7~Sample 19, Sample 101, Sample 102, Sample 105》 The following cutting test 3 and cutting test 4 were performed using tools (shape: DNGA150408) composed of cubic boron nitride sintered bodies of samples 7 to 19, 101, 102, and 105, in which the content of cubic boron nitride particles in the cubic boron nitride sintered bodies was greater than 45 volume % and less than 65 volume %. The conditions of cutting test 3 and cutting test 4 correspond to high-efficiency machining of high-hardness steel.
[0164] Cutting test 3: evaluation of chip resistance Cutting material: High hardness steel SCM415H round bar, five grooves, HRC62, diameter 100mm × length 300mm Cutting speed: V = 150m / min. Feed: f = 0.15 mm / rev. Incision: ap = 0.2 mm Wet / Dry: Dry Cutting method: intermittent cutting The blade tip is observed every 0.15km of cutting distance, and the amount of blade tip shedding is measured. The amount of blade tip shedding is set as the retreat amplitude in the back tool face direction caused by wear from the position of the blade tip ridgeline before cutting. In the case of a defect, the size of the defect is taken as the amount of shedding. The cutting evaluation is terminated at the time point when the blade tip shedding exceeds 0.04mm or the cutting distance is 5.0km, and the amount of blade tip shedding is measured. The smaller the amount of shedding, the better the defect resistance and the longer the tool life. In "Cutting Test 3" in Table 4, the case where the blade tip shedding is less than 0.04mm when the cutting distance is 5.0km is recorded as "A", and the case where the blade tip shedding exceeds 0.04mm before the cutting distance reaches 5.0km or the blade tip shedding exceeds 0.04mm when the cutting distance is 5.0km is recorded as "B". "A" indicates excellent defect resistance and long tool life. "B" indicates insufficient defect resistance and short tool life.
[0165] Cutting test 4: Wear resistance evaluation Cutting material: High hardness steel SCM415H round bar, no groove, HRC62, diameter 100mm × length 300mm Cutting speed: V = 120m / min. Feed: f = 0.1 mm / rev. Incision: ap = 0.15 mm Wet / Dry: Wet Cutting method: continuous cutting The blade tip is observed every 0.5 km of cutting distance, and the amount of blade tip shedding is measured. The amount of blade tip shedding is set as the retreat amplitude in the back tool face direction caused by wear from the position of the blade tip ridgeline before cutting. The cutting evaluation is terminated when the blade tip shedding exceeds 0.04 mm or the cutting distance is 10.0 km, and the amount of blade tip shedding is measured. The smaller the shedding amount, the better the wear resistance and the longer the tool life. In "Cutting Test 4" in Table 4, the case where the blade tip shedding amount is less than 0.04 mm when the cutting distance is 10.0 km is recorded as "A", and the case where the blade tip shedding amount exceeds 0.04 mm before the cutting distance reaches 10.0 km or the blade tip shedding amount exceeds 0.04 mm when the cutting distance is 10.0 km is recorded as "B". "A" indicates excellent wear resistance and long tool life. "B" indicates insufficient wear resistance and short tool life.
[0166] In this embodiment, when the results of both cutting test 3 and cutting test 4 are "A", the tool life is determined to be long. When the results of one or both of cutting test 3 and cutting test 4 are "B", the tool life is determined to be insufficient.
[0167]
[0168] The cubic boron nitride sintered bodies and tools of samples 7 to 19 correspond to the examples, and the cubic boron nitride sintered bodies and tools of samples 101, 102, and 105 correspond to the comparative examples. It was confirmed that the tools of samples 7 to 19 were excellent in defect resistance and wear resistance, and the tool life was long. It was confirmed that the tools of samples 101, 102, and 105 were insufficient in defect resistance and wear resistance, and the tool life was insufficient.
[0169] 《Sample 20~Sample 25, Sample 106, Sample 107》 The following cutting test 5 and cutting test 6 were performed using tools (shape: DNGA150408) composed of cubic boron nitride sintered bodies of samples 20 to 25, sample 106, and sample 107, in which the content of cubic boron nitride particles in the cubic boron nitride sintered bodies was greater than 65 volume % and less than 80 volume %. The conditions of cutting test 5 and cutting test 6 correspond to high-efficiency machining of high-hardness steel.
[0170] Cutting test 5: evaluation of chip resistance Cutting material: High hardness steel SCM415H round bar, five grooves, HRC62, diameter 100mm × length 300mm Cutting speed: V = 150m / min. Feed: f = 0.2 mm / rev. Incision: ap = 0.3 mm Wet / Dry: Dry Cutting method: intermittent cutting The blade tip is observed every 0.15km of cutting distance, and the amount of blade tip shedding is measured. The amount of blade tip shedding is set as the retreat amplitude in the back tool face direction caused by wear from the position of the blade tip ridgeline before cutting. In the case of a defect, the size of the defect is taken as the amount of shedding. The cutting evaluation is terminated at the time point when the blade tip shedding exceeds 0.04mm or the cutting distance is 5.0km, and the amount of blade tip shedding is measured. The smaller the amount of shedding, the better the defect resistance and the longer the tool life. In "Cutting Test 5" in Table 5, the case where the blade tip shedding is less than 0.04mm when the cutting distance is 5.0km is recorded as "A", and the case where the blade tip shedding exceeds 0.04mm before the cutting distance reaches 5.0km or the blade tip shedding exceeds 0.04mm when the cutting distance is 5.0km is recorded as "B". "A" indicates excellent defect resistance and long tool life. "B" indicates insufficient defect resistance and short tool life.
[0171] Cutting test 6: Wear resistance evaluation Cutting material: High hardness steel SCM415H round bar, no groove, HRC62, diameter 100mm × length 300mm Cutting speed: V = 120m / min. Feed: f = 0.15 mm / rev. Incision: ap = 0.2 mm Wet / Dry: Wet Cutting method: continuous cutting The blade tip is observed every 0.5 km of cutting distance, and the amount of blade tip shedding is measured. The amount of blade tip shedding is set as the retreat amplitude in the back tool face direction caused by wear from the position of the blade tip ridgeline before cutting. The cutting evaluation is terminated when the blade tip shedding exceeds 0.04 mm or the cutting distance is 10.0 km, and the amount of blade tip shedding is measured. The smaller the shedding amount, the better the wear resistance and the longer the tool life. In "Cutting Test 6" in Table 5, the case where the blade tip shedding amount is less than 0.04 mm when the cutting distance is 10.0 km is recorded as "A", and the case where the blade tip shedding amount exceeds 0.04 mm before the cutting distance reaches 10.0 km or the blade tip shedding amount exceeds 0.04 mm when the cutting distance is 10.0 km is recorded as "B". "A" indicates excellent wear resistance and long tool life. "B" indicates insufficient wear resistance and short tool life.
[0172] In this embodiment, when the results of both cutting test 5 and cutting test 6 are "A", the tool life is determined to be long. When the results of one or both of cutting test 5 and cutting test 6 are "B", the tool life is determined to be insufficient.
[0173]
[0174] The cubic boron nitride sintered bodies and tools of samples 20 to 25 correspond to the examples, and the cubic boron nitride sintered bodies and tools of samples 106 and 107 correspond to the comparative examples. It was confirmed that the tools of samples 20 to 25 were excellent in defect resistance and wear resistance, and had long tool life. It was confirmed that the tools of samples 106 and 107 were insufficient in defect resistance and wear resistance, and had insufficient tool life.
[0175] <Evaluation of Cubic Boron Nitride Sintered Body> The following evaluations were performed on Sample 6, Sample 11, Sample 22, Samples 26 to 32, Sample 101, Sample 103, and Sample 106.
[0176] 《The Presence or Absence of the First Phase at the Interface between Cubic Boron Nitride Particles and Binding Phase》 In the cubic boron nitride sintered body of each sample, it is confirmed whether the first phase exists at the interface between the cubic boron nitride particles and the binding phase. The specific measurement method is as described in Implementation Example 1. The results are shown in the "Presence or absence of the first phase at the binding phase interface" column of "Cubic boron nitride sintered body" in Table 6. "Presence" indicates that the first phase exists at the interface between the cubic boron nitride particles and the binding phase. "Absence" indicates that the first phase does not exist at the interface between the cubic boron nitride particles and the binding phase.
[0177] 《First phase thickness》 The thickness of the first phase was measured in the cubic boron nitride sintered body of each sample. The specific measurement method is as described in Embodiment 1. The results are shown in the "Thickness of First Phase" column of "Cubic Boron Nitride Sintered Body" in Table 6.
[0178] 《Tungsten content and cobalt content in the first phase》 In the cubic boron nitride sintered body of each sample, the tungsten content and the cobalt content were measured to confirm which one was greater. The results are shown in the "First Phase W, Co Content" column of "Cubic Boron Nitride Sintered Body" in Table 6. "W>Co" means that the tungsten content is greater than the cobalt content. "Co>W" means that the cobalt content is greater than the tungsten content.
[0179]
[0180] <Evaluation of the tool> 《Cutting Test 5》 Cutting Test 5 was performed under the following conditions using a tool (shape: DNGA150408) composed of the cubic boron nitride sintered body of Sample 6, Sample 103, Sample 27, and Sample 28.
[0181] Cutting material: High hardness steel SCM415H round bar, five grooves, HRC62, diameter 100mm × length 300mm Cutting speed: V = 150m / min. Feed: f = 0.15 mm / rev. Incision: ap = 0.2 mm Wet / Dry: Dry Cutting method: intermittent cutting The blade tip is observed every 0.2 km of cutting distance, and the amount of blade tip shedding is measured. The amount of blade tip shedding is set as the retreat amplitude in the back direction of the tool face caused by wear from the position of the blade tip ridgeline before cutting. In the case of a defect, the size of the defect is taken as the amount of shedding. The cutting evaluation is terminated when the amount of blade tip shedding exceeds 0.03 mm or the cutting distance reaches 2.0 km, and the amount of blade tip shedding is measured. The smaller the shedding amount, the better the defect resistance and the longer the tool life. In "Cutting Test 5" of Table 7, the case where the amount of blade fall-off at the cutting edge when the cutting distance is 2.0 km is 0.01 mm or less is recorded as "A", the case where the amount of blade fall-off exceeds 0.01 mm and is 0.02 mm or less is recorded as "B", the case where the amount of blade fall-off exceeds 0.02 mm and is 0.03 mm or less is recorded as "C", and the case where the amount of blade fall-off exceeds 0.03 mm, or the case where the amount of blade fall-off exceeds 0.03 mm before reaching the cutting distance of 2.0 km is recorded as "D". "A" indicates excellent defect resistance and long tool life.
[0182]
[0183] 《Cutting Test 6》 Cutting Test 6 was performed under the following conditions using a tool (shape: DNGA150408) composed of the cubic boron nitride sintered body of Sample 11, Sample 101, Sample 26, Sample 30, Sample 31, and Sample 32.
[0184] Cutting material: High hardness steel SCM415H round bar, five grooves, HRC62, diameter 100mm × length 300mm Cutting speed: V = 150m / min. Feed: f = 0.2 mm / rev. Incision: ap = 0.3 mm Wet / Dry: Dry Cutting method: intermittent cutting Evaluation criteria A to D are the same as those in cutting test 5. The results are shown in Table 8.
[0185]
[0186] 《Cutting Test 7》 Cutting Test 7 was performed under the following conditions using a tool (shape: DNGA150408) composed of the cubic boron nitride sintered body of Sample 22, Sample 106, and Sample 29.
[0187] Cutting material: High hardness steel SCM415H round bar, five grooves, HRC62, diameter 100mm × length 300mm Cutting speed: V = 150m / min. Feed: f = 0.25 mm / rev. Incision: ap = 0.4 mm Wet / Dry: Dry Cutting method: intermittent cutting Evaluation criteria A to D are the same as those in cutting test 5. The results are shown in Table 9.
[0188]
[0189] As mentioned above, although the embodiment and the example of this disclosure were described, it is also planned from the beginning that the configurations of each embodiment and the example described above are appropriately combined or variously modified.
[0190] The embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present invention is indicated by the claims rather than the embodiments and is intended to include all modifications within the scope and meaning equivalent to the claims.
Claims
1. A cubic boron nitride sintered body comprising cubic boron nitride particles, a binding phase and a first phase, wherein: The content of the cubic boron nitride particles in the cubic boron nitride sintered body is 25% by volume or more and 80% by volume or less. The bonding phase comprises one or more first compounds and one or both of solid solutions derived from the first compounds, wherein the first compounds are composed of at least one element selected from the group consisting of titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, aluminum, and silicon, and at least one element selected from the group consisting of nitrogen, carbon, boron, and oxygen, The first phase comprises cobalt, tungsten and at least one first element selected from the group consisting of the elements comprised by the bonding phase, The total content of cobalt and tungsten in the cubic boron nitride sintered body is 1.0 mass % or more and 6.0 mass % or less, The binding phase is composed of a plurality of binding phase particles, The plurality of binding phase particles include more than 50% of first binding phase particles on a number basis, The surface of the first binding phase particle contains more than 50% by area of the first region, The first region is a region in contact with the first phase.
2. The cubic boron nitride sintered body according to claim 1, wherein: The plurality of binding phase particles contain more than 50% of the second binding phase particles on a number basis, The surface of the second binding phase particle contains more than 75% by area of the first region.
3. The cubic boron nitride sintered body according to claim 1 or 2, wherein: The bonding phase includes at least one element selected from the group consisting of titanium, chromium, aluminum, carbon, nitrogen, and boron.
4. The cubic boron nitride sintered body according to any one of claims 1 to 3, wherein The first element includes at least one element selected from the group consisting of aluminum, carbon, nitrogen, boron, and silicon.
5. The cubic boron nitride sintered body according to any one of claims 1 to 4, wherein The first phase does not exist at the interface between the cubic boron nitride particles and the binding phase.
6. The cubic boron nitride sintered body according to any one of claims 1 to 5, wherein The thickness of the first phase is 20 nm or less.
7. The cubic boron nitride sintered body according to any one of claims 1 to 6, wherein The tungsten content of the first phase is greater than the cobalt content of the first phase.
8. A tool, wherein: The tool is a tool comprising the cubic boron nitride sintered body according to any one of claims 1 to 7.
Citation Information
Patent Citations
Cubic boron nitride-based sintered compact-made cutting tool
JP2020028929A
cBN sintered compact and cutting tool
CN107001154A
Cubic boron nitride sintered body and coated cubic boron nitride sintered body
CN107207362A
Sintered cubic boron nitride and cutting tool comprising same
CN115803468A
Cutting tool made of cubic crystal boron nitride-based sintered body
JP2020131293A
